Plasmidic versus Insertional Cloning of Heterologous Genes in Mycobacterium bovis BCG: Impact on In Vivo Antigen Persistence and Immune Responses - Méderlé, I. (American Society for Microbiology, 2002)
Bivalent recombinant strains of Mycobacterium bovis BCG (rBCG) expressing the early regulatory nef and the structural gag(p26) genes from the simian immunodeficiency virus (SIV) SIVmac251 were engineered so that both genes were cotranscribed from a synthetic operon. The expression cassette was cloned into a multicopy-replicating vector, and the expression levels of both nef and gag in the bivalent rBCG(nef-gag) strain were found to be comparable to those of monovalent rBCG(nef) or rBCG(gag) strains. However, extrachromosomal cloning of the nef-gag operon into a replicative plasmid resulted in strains of low genetic stability that rapidly lost the plasmid in vivo. Thus, the nef-gag operon was inserted site specifically into the BCG chromosome by means of mycobacteriophage Ms6-derived vectors. The resulting integrative rBCG(nef-gag) strains showed very high genetic stability both in vitro and in vivo. The in vivo expression of the heterologous genes was much longer lived when the expression cassette was inserted into the BCG chromosome. In one of the strains obtained, integrative cloning did not reduce the expression levels of the genes even though a single copy was present. Accordingly, this strain induced cellular immune responses of the same magnitude as that of the replicative rBCG strain containing several copies of the genes.